Surat Kuasa Mutlak pada Perjanjian Pengikatan Jual Beli Hak Atas Tanah - Gedion Ardana Reswari (Fakultas Hukum Universitas Islam Jember, 2014)
Binding sale and purchase agreement is a treaty right to sui generis obligatoir that because his character is authentic written agreement made before a notary public , in the areas of property, specifically land rights object . Ownership is not switched to the seller and a preliminary agreement ( accesoir ). Absolute power of attorney is essentially an authorization can not be withdrawn and the power management of the transition is simply the act of land rights . Special letter there are 2 kinds of power of attorney that is absolutely independent and absolute power of attorney into a single unit substantially in agreement .The absolute power of attorney into a single unit in the principal agreement is not contrary to the instructions of the Minister of Home Affairs No. 14 of 1982 on the prohibition of the use of the absolute power of attorney as the transfer of land rights , otherwise if the absolute power of attorney is a stand-alone contrary to instructions of the Minister of Home Affairs No. 14 of 1982.